Structural adjustment, public policy and administration in the Caribbean - La Guerre, John ed. (U.W.I. School of Continuing Education St. AugustineTT, 1994)
Deals with the various issues connected to and deriving from the process of structural adjustment in the Caribbean. Suggests changes that need to be made in the economic, political and administrative systems to bring about the restructuring desired. Discusses the reform of the public sector, decentralization, the impact of adjustment on the unions and the kind of policy that has to be followed in societies divided on cultural bases.